Application of HOTS (High Order Thinking Skill) in Science Learning During the Pandemic - Nuryunita Dewantari; Suwito Singgih; Riva Ismawati (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research to know application of HOTS based science learning during the pandemic. The research method used is a literature study method, in which data is collected without going directly to the field and meeting directly with the respondents. The results of this study indicate that the application of HOTS in learning is able to solve problems and find solutions to problems, so as to bring up new discoveries that can be useful. In addition, the application of HOTS in learning is also able to improve student learning outcomes. Based on the results of research that have been studied can be concluded that the application of HOTS learning during the pandemic is able to improve student learning outcomes and make learning more meaningful.